The Application of Reconciliation in Muslim Divorce Cases Caused by the Domestic Violence: An Analysis Between Islamic and Malaysian Law - Nadzrah Ahmad; Rahmawati Mohd Yusoff; Rohaiza Abd Rokis; Wan Mazwati Wan Yusoff; Adibah Abdul Rahim; Norzulaili Mohd Ghazali (Human Resource Management Academic Research Society, 2024)
Indexed by ERA